Estimation of Carbon Stock and Emission, and Life Cycle Assessment of Malaysian Hevea for Establishing National Carbon Inventory - Chung, Irene (2004)
The study utilises two computer spreadsheet models to estimate both carbon sequestered by Malaysian rubber plantation ecosystems, and carbon stocks and emissions from harvested rubber wood products (furniture, medium density fibreboard, rubber gloves and tyres). Changes in the net carbon balance in Malaysian rubber ecosystems are related to the total rubber hectarage, age class structure, age class dynamics, and total biomass, rate of harvesting and production and utilization of the products. The Carbon Sequestration Model and Harvested Wood Products Model were used to estimate the carbon budget of the ecosystem and also the carbon fate in the latex and wood products throughout their life span. From the life cycle assessment of one-hectare of rubber, we project that carbon storage in biomass and products could last up to 63 years before it returns to a carbon neutral situation. At the national level, the rate of carbon stocks were projected to decrease from 241,748 kTC in 1991 to 231,541 kTC in 1996. The declining trend (between 1991 and 1996) was estimated to continue in the projected years (2004 to 2020). Carbon stocks registered at 105,354 kTC (year 2013), followed by 90,748 kTC (year 2017) and eventually amounted to 80,797 kTC (year 2020). Harvested rubber products played an important role in the process of delaying the return of the carbon to the atmosphere. Net emission could be minimized through appropriate pollution control technologies in landfills, increasing product use efficiency, recycling and increasing product longevity. Stock to emission ratio (SER) is described and proven to be a useful measure to determine the longevity of an industry.